MEMBANGUN BUDAYA LITERASI DI SEKOLAH DASAR NEGERI TRANGSAN 02 GATAK KABUPATEN SUKOHARJO DALAM MENDUKUNG KEBERHASILAN KEGIATAN BELAJAR ABAD 21 - Juminingsih Juminingsih (Jurnal Pendidikan Ilmu Sosial, 2019)
Primary school is one of the levels of education whose task is to realize the national education goals. In order to achieve this goal the school must have good quality. One effort to improve the quality of schools is to support facilities and infrastructure and improve the reading culture. This Best Practice is designed to support the work that the author has done as the principal. This study aims to describe the initial conditions of the school, explain the efforts, constraints and ways to overcome them in building a culture of literacy to support the success of teaching learning activities in explaining the results that have been achieved. The results showed that 1) The initial conditions of literacy were still low; 2) How to build a culture of literacy began with the procurement of facilities and infrastructure followed by habituation; 3) Constraints faced included facilitators, costs, and interests of students; 4) How to overcome existing problems namely with financial donations, attending workshops and holding tutoring and extracurricular activities; 5) The results achieved through the development of a literacy culture, namely the school can win several race champions. Suggestions are given that the government through the education office should be more focused on addressing issues related to literacy in primary schools and for principals to be role models in literacy.